2013
DOI: 10.1002/nml.21072
|View full text |Cite
|
Sign up to set email alerts
|

Degree and Direction of Paid Employee/Volunteer Interchange in Nonprofit Organizations

Abstract: This study builds on an earlier one (Handy, Mook, and Quarter 2008)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…The most basic distinction that these professionals need to make in working with volunteers is whether the tasks assigned to volunteers are the same as, or different than, those performed by paid staff in the organization. As Handy, Mook, and Quarter (2008) and their colleagues (Chum, Mook, Handy, Schugurensky, & Quarter, 2013) observe, some interchangeability between the work performed by paid staff and volunteers is endemic to work life in many organizations and is to be expected. To the extent that volunteers perform the same tasks as paid staff, the universalistic practices, which are rooted in the metaphor of the workplace, would seem to apply, including job descriptions, written policies and procedures, and orientation and supervision, among others (see Tables 1 and 2).…”
Section: Discussion: Applying Principles To Practicementioning
confidence: 99%
“…The most basic distinction that these professionals need to make in working with volunteers is whether the tasks assigned to volunteers are the same as, or different than, those performed by paid staff in the organization. As Handy, Mook, and Quarter (2008) and their colleagues (Chum, Mook, Handy, Schugurensky, & Quarter, 2013) observe, some interchangeability between the work performed by paid staff and volunteers is endemic to work life in many organizations and is to be expected. To the extent that volunteers perform the same tasks as paid staff, the universalistic practices, which are rooted in the metaphor of the workplace, would seem to apply, including job descriptions, written policies and procedures, and orientation and supervision, among others (see Tables 1 and 2).…”
Section: Discussion: Applying Principles To Practicementioning
confidence: 99%
“…Several recent studies have tackled the question of whether volunteer labor and paid labor are substitutes or complements (Chum et al ; Handy, Mook, and Quarter ; Simmons and Emanuele ; Stine ). Although these studies report mixed results, the mere perception of job vulnerability may have the potential to incite volunteer‐staff conflict.…”
Section: Dynamics Of Volunteer‐staff Interactions: From Satisfaction mentioning
confidence: 99%
“…A study of Canadian nonprofits found that the interchange of volunteers and paid labourers was widespread among nonprofit organizations, but that it was limited to a specific set of tasks related to customer service and to tasks requiring general skills (Chum et al, 2013). This accounted for about one-eighth of all tasks in one study (Handy et al, 2008) and about one-quarter of tasks in another (Chum et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a growing body of literature that examines the prevalence of interchange between volunteers and paid staff and the characteristics related to this phenomenon in various settings, including hospitals (Handy, Mook, & Quarter, 2008;Handy & Srinivasan, 2005), nonprofit organizations (Chum, Mook, Handy, Schugurensky, & Quarter, 2013;Handy et al, 2008), and public sector and government agencies (Brudney, 1990;Brudney & Gazley, 2002;Brudney & Kellough, 2000). A key driver for research on interchangeability is the concern that the substitution of paid staff by volunteers over the long-term could result in a decrease in paid jobs within an organization and thus be viewed as a form of labour exploitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation